2003
DOI: 10.1097/00001756-200303030-00033
|View full text |Cite
|
Sign up to set email alerts
|

Dose???response of cyclosporin A in attenuating traumatic axonal injury in rat

Abstract: Cyclosporin A has emerged as a promising therapeutic agent in traumatic brain injury (TBI), although its precise neuroprotective mechanism is unclear. Cyclosporin A, given as a single-dose intrathecal bolus, has previously been shown to attenuate mitochondrial damage and reduce axonal injury in experimental TBI. We assessed the effect of a range of intravenous cyclosporin A doses upon axonal injury attenuation to determine the ideal dose. Rats were subjected to experimental TBI and given one of five intravenou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(41 citation statements)
references
References 0 publications
1
40
0
Order By: Relevance
“…177,178 Indeed, compared with FK506, a related immunosuppressant that inhibits calcineurin as effectively as CyA does, 169,179 CyA was superior in protecting against ischemic damage [177][178][179][180] and hypoglycemic brain injury, 181 presumably because of the superior ability of CyA to inhibit the mitochondrial permeability transition. 180 In addition to the suggestion that CyA completely inhibits excitotoxin-induced neuronal cell death, 182 there is also a dose-dependent inhibition of amyloid precursor protein accumulation 183 and of traumatic axonal injury after TBI, 184 which may account for the reduced number of disconnected and dysfunctional axons following impact acceleration TBI. [185][186][187][188] In clinical studies, phase II trials of CyA in TBI 189 have shown in the ascending dose study that patients with TBI demonstrated more rapid clearance and a wider distribution of CyA metabolites than other populations, thus complicating accurate dose determination for further trials.…”
Section: Cyclosporinmentioning
confidence: 99%
“…177,178 Indeed, compared with FK506, a related immunosuppressant that inhibits calcineurin as effectively as CyA does, 169,179 CyA was superior in protecting against ischemic damage [177][178][179][180] and hypoglycemic brain injury, 181 presumably because of the superior ability of CyA to inhibit the mitochondrial permeability transition. 180 In addition to the suggestion that CyA completely inhibits excitotoxin-induced neuronal cell death, 182 there is also a dose-dependent inhibition of amyloid precursor protein accumulation 183 and of traumatic axonal injury after TBI, 184 which may account for the reduced number of disconnected and dysfunctional axons following impact acceleration TBI. [185][186][187][188] In clinical studies, phase II trials of CyA in TBI 189 have shown in the ascending dose study that patients with TBI demonstrated more rapid clearance and a wider distribution of CyA metabolites than other populations, thus complicating accurate dose determination for further trials.…”
Section: Cyclosporinmentioning
confidence: 99%
“…Recently, the role of cyclosporin A (CsA) as a neuroprotectant has been documented in several animal models of TBI (Alessandri et al, 2002;Okonkwo et al, , 2003Signoretti et al, 2004;Sullivan et al, 1999Sullivan et al, , 2000b. CsA transiently inhibits the opening of the mitochondrial permeability transition pore by unbinding mitochondrial matrix cyclophillin from the pore (Broekemeier et al, 1989;Broekemeier and Pfeiffer, 1995;Szabò and Zoratti, 1991), and thus protects mitochondria in the face of increased intracellular calcium.…”
Section: Introductionmentioning
confidence: 99%
“…It is further supported by the role of cyclosporine A and FK506, which inhibit calcineurins to provide neuroprotection and improve outcomes after TBI. 44,48 On the other hand, TBI-induced downregulation of calcineurins may be destructive. Previously we reported that fluid percussion TBI significantly decreased the expression of glial cell line-derived neurotrophic factor (GDNF) in rat hippocampi, whereas grafted human neural stem cells produced GDNF and rescued the cognitive deficit.…”
Section: Discussionmentioning
confidence: 99%